Sound transmission loss characteristics of sandwich aircraft panels: Influence of nature of core. (January 2017) - Arunkumar, MP; Pitchaimani, Jeyaraj; Gangadharan, KV; Lenin Babu, MC
Sandwich panel which has a design involving acoustic comfort is always denser and larger in size than the design involving mechanical strength. The respective short come can be solved by exploring the impact of core geometry on sound transmission characteristics of sandwich panels. In this aspect, the present work focuses on the study of influence of core geometry on sound transmission characteristics of sandwich panels which are commonly used as aircraft structures. Numerical investigation has been carried out based on a 2D model with equivalent elastic properties. The present study has found that, for a honeycomb core sandwich panel in due consideration to space constraint, better sound transmission characteristics can be achieved with lower core height. It is observed that, for a honeycomb core sandwich panel, one can select cell size as the parameter to reduce the weight with out affecting the sound transmission loss. Triangular core sandwich panel can be used for low frequency application due to its increased transmission loss. In foam core sandwich panel, it is noticed that the effect of face sheet material on sound transmission loss is significant and this can be controlled by varying the density of foam.